Evaluation of sensitivity and spesitivity as COVID–19 screening method - Atikah Nurhesti; Solikhah Solikhah; Siti Nur Djannah (Intelektual Pustaka Media Utama, 2021)
Coronavirus disease 2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Antibody rapid test is one of the COVID-19 screening tests that can be used in the community. The accuracy of the rapid antibody methods needs to be appropriately assessed, it is necessary to carry out a diagnostic accuracy study using a pairwise sensitivity and specificity analysis. This research aimed to assess the sensitivity and specificity of COVID-19 rapid tests, also assesses positive predictive value (PPV) and negative predictive value (NPV) of the rapid antibody test as a method of screening for COVID-19 in Sleman Regency, Indonesia. In total, 118 respondents who have contact with COVID-19 patients and have symptoms were enrolled in this study. The study was conducted on 118 patients who had been in contact with confirmed COVID-19 118 patients who met the close contact criteria were conducted a rapid antibody test. 64.41% patients were reactive. Real-time polymerase chain reaction (RT PCR) as a gold standard was also carried out for all patients and 63.56% affirmed positive for COVID-19. The sensitivity value was 97.33%, and the specificity value was 93.02%, while the positive predictive value (NPP) was 96.05%, and the negative predictive value (NPN) was 95.24%. These results meet the minimum recommendations for the screening method.